Analisis Faktor-Faktor yang mempengaruhi Underpricing Saham Saat Initial Publik Ofering (IPO) pada Perusahaan Sektor Non Keuangan yang terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Kharisma, Jihan; Adnan Pratama, Ifanny (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To determine the effect of Liquidity, Profitability, and Leverage on Stock Returns in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Background Problems: At the time of IPO there is often a difference in stock prices when traded on the stock exchange. The stock price at the time of IPO tends to be lower than the stock price on the stock exchange on the first day (closing price). Novelty: Re-examining the same variables with different sectors and different research years. Research Methods: Using quantitative methods with secondary data types in the form of financial statements, using purposive sampling methods and SPSS multiple linear regression data analysis techniques. Finding/Results: Company shares in the primary market do not only pay attention to the company's financial information, but also information on non-financial factors is needed that the reputation of underwriters and the percentage of stock offerings affect underpricing at the time of IPO. Conclusion: Liquidity as measured by Current Ratio (CR) and Debt to Equity Ratio (DER) has no significant effect on Stock Returns, Profitability as measured by Return on Assets (ROA) has a significant effect on Stock Returns and simultaneously Liquidity, Profitability and Leverage significant effect on Stock Return.